Analysis of the Merdeka Curriculum in Physical Education Learning at Senior High School - Kimi Aditya Rizki; Tite Juliantine; Agus Gumilar (Universitas Negeri Semarang, 2026)
This study examines the implementation of the Merdeka Curriculum in Physical Education, Sports, and Health learning at the senior high school level. The research focuses on three key aspects: planning, classroom implementation, and assessment practices. A qualitative case study design was applied in two schools, Jatinangor High School and Al-Aqsha High school Plus. Data were collected through semi structured interviews, direct classroom observations, and document analysis, including the Education Unit Operational Curriculum, Learning Objectives Flow, and teaching modules. Data were analyzed using the stages of reduction, display, and conclusion drawing, with source and technique triangulation to ensure credibility. The findings show that teachers have aligned learning plans with Learning Outcomes and translated them into structured objectives and contextual teaching modules. Instruction emphasizes student centered learning through differentiated activities based on students’ physical abilities and participation levels. Teachers act as facilitators who guide active engagement and skill development. Assessment practices apply authentic and continuous evaluation covering attitudes, knowledge, and motor skills through observation, performance tasks, and reflection. Institutional support, including principal supervision and adequate sports facilities, strengthens curriculum implementation. However, uneven access to training and variations in teacher readiness remain challenges. Overall, the Merdeka Curriculum in Physical Education demonstrates strong potential to improve learning quality when supported by consistent professional development and school level commitment.